Risk factors for AIDS-defining illnesses among a cohort of poorly adherent people living with HIV/AIDS in Atlanta, Georgia - Chow, Jeremy Y. (AIDS Care, 2015)
In order to achieve the programmatic goals established in the National HIV/AIDS Strategy, virologic suppression remains the most important outcome within the HIV care continuum for individuals receiving antiretroviral therapy (ART). Therefore, clinicians have dedicated substantial resources to improve adherence and clinic retention for individuals on ART; however, these efforts should be focused first on those most at risk of morbidity and mortality related to AIDS. Our study aimed to characterize the factors that are associated with AIDS-defining illnesses (ADIs) amongst people living with HIV (PLHIV) who are poorly adherent or retained in care in order to identify those at highest risk for poor clinical outcomes. We recruited 99 adult PLHIV with a history of poor adherence to ART, poor clinic attendance, or unsuppressed viral load from the Infectious Disease Program (IDP) of the Grady Health System in Atlanta, GA between January and May of 2011 to participate in a survey investigating the acceptability of a financial incentive for improving adherence. Clinical outcomes including the number of ADI episodes in the last five years, viral loads, and CD4 counts were abstracted from medical records. Associations between survey items and number of ADIs were performed using Chi-square analysis. In our study, 36.4% of participants had ≥1 ADI in the last five years. The most common ADIs were Pneumocystis jirovecii pneumonia, recurrent bacterial pneumonia, and esophageal candidiasis. Age <42.5 years (OR 2.52, 95%CI 1.08-5.86), Male gender (OR 3.51, 95%CI 1.08-11.34), CD4 nadir <200 cells/µL (OR 11.92, 95%CI 1.51-94.15), unemployment (OR 3.54, 95%CI 1.20-10.40), and travel time to clinic <30 minutes (OR 2.80, 95%CI 1.20-6.52) were all significantly associated with a history of ≥1 ADI in the last five years. Awareness of factors associated with ADIs may help clinicians identify which poorly adherent PLHIV are at highest risk for HIV-related morbidity.